Study of chemical and physical properties of apples dried in a convective drier. - Cruz, AC (2012)
The present study evaluates the effects of drying on apple slices from two varieties, Golden Delicious and Granny Smith, which were analyzed in terms of physical and chemical properties. The tests involved the determination of moisture, acidity, soluble solids, colour and texture. Trials were performed in a convective hot air dryer for different temperatures of 30, 40, 50 and 60 ° C. The results showed that the final moisture of the two varieties of apples was around 3 % (wet basis). With regards to acidity, the variety Granny Smith was found to be more acid than the Golden Delicious. The soluble solids are present, in general, in greater amounts in the variety Granny Smith. As to the colour, this varied very considerably from the fresh apples to the dried ones. Apples of the variety Golden Delicious presented a higher intensity of yellow (b* > 0) and red (a* > 0). However, in comparison to the variety Granny Smith the Golden Delicious presents, in general, smaller total colour differences. The textural attributes evaluated were hardness, adhesiveness, elasticity, cohesiveness and chewiness. However, the results for adhesiveness were very close to zero showing that these products do not have adhesiveness, as it happens with other fruits. It was also found that the fresh apples have a much higher hardness, when compared to the dried samples. Elasticity, on the other hand, was kept approximately constant regardless of the variety or state. Cohesiveness was higher in the fresh apples, and for the dried ones was higher for variety Golden. Finally, chewiness was higher for the fresh apples in comparison to the dried ones, and was higher for Golden Delicious when compared with Granny Smith.